John Calvin’s Mistake? A Dogmatic Assessment of Calvin’s Revisions of Nicene Trinitarianism - McGraw, Ryan M. (Reformed theological review, 2025)
Though Calvin’s views of eternal generation became widely accepted in Reformed thought from at least the nineteenth century onward, many modern theologians have not yet realized the seismic shift that he introduced into classic Trinitarian theology. It is important to alert modern readers to the unusual place of Calvin’s views in Christian history, as well as the potential outcomes of his move. After rehabilitating some historical questions about Calvin’s Trinitarian theology and exegesis and raising some contemporary questions about both, this essay evaluates Calvin’s revised form of eternal generation and argues that John Calvin’s views of eternal generation do not cohere well with standard Christian Trinitarian theology and exegesis.